The association of loneliness and social isolation with healthcare utilization in Denmark: Julie Christiansen. (25th October 2022) - Christensen, J; Pedersen, SS; Andersen, CM; Qualter, P; Lund, R; Lasgaard, M
Abstract: Objectives: The present prospective cohort study investigated the association of loneliness and social isolation (SI) with healthcare utilization (HCU) in the general population over time. Methods: Data from the 2013 Danish "How are you?' survey (n = 29, 472) were combined with individual-level register data from the National Danish Patient Registry and the Danish National Health Service Registry over a 6-year follow-up period (2013-2018). Negative binomial regression analyses were performed while adjusting for baseline demographics and chronic disease. Results: Loneliness measured at baseline was significantly associated with more GP contacts (incident-rate ratio (IRR) = 1.03, 95% confidence interval (CI) [1.02, 1.04]), more emergency treatments (IRR = 1.06, 95% CI [1.03, 1.10]), more emergency admissions (IRR = 1.06, 95% CI [1.03, 1.06]), and hospital admission days (IRR=1.05, 95% CI [1.00, 1.11]) across the 6-year follow-up period. No significant associations were found between social isolation and HCU with one minor exception, in which SI was associated with fewer planned outpatient treatments (IRR = .97, 95% CI [.94, .99]). Conclusions: Our findings suggest that loneliness is a risk factor for certain types of HCU, independent of social isolation, baseline demographics, and chronic disease. Key messages: The findings suggest that lonely individuals are slightly overrepresented within the healthcare system. In contrast, social isolation does not affect the use of health care services. The association between loneliness and health care utilization is complex and there is a need for future studies to investigate the mechanisms underlying the association.